STUDI DESKRIPTIF PEMENUHAN TUGAS-TUGAS PENGAMBILAN KEPUTUSAN KARIER PADA ANAK BUNGSU - Cahaya, Wella Ayu (University of Surabaya, 2016)
Youngest children has a characteristic that tend to depend on others, but on the other hand there are youngest children who have a high motivation. These characteristics can influence the career decision-making, especially in the youngest children who depend on others so that decisions are not in accordance with their conditions. In fact, career is an important element that is used by humans to equipping life. Having a career is also one of the developmental tasks of a teenager. The purpose of this study was to describe the fulfillment of career decision-making tasks in the youngest children. The tasks in career decision making is orientation, self-exploration, broad and depth exploration of the environment, identity status, and commitment. This study found the fulfillment of the tasks of career decision-making is divided into three patterns, they are optimally fulfill all tasks (N = 16), optimally fulfill several tasks (N = 104), and yet optimally fulfill all tasks (N = 6). Most task can be fulfilled optimally by the youngest child is commitment and a task most not fulfilled optimally is selfexploration. The distinguishes between three patterns fulfillment is the habit of making decisions in everyday life, the role of teachers, and the response to the dissents.